Nina Simone's gum - Ellis, Warren 1968- (Faber & Faber Limited, 2021)
On Thursday 1 July, 1999, Nina Simone gave a rare performance as part of Nick Cave's Meltdown Festival. After the show, in a state of awe, Warren Ellis crept onto the stage, took Simone's piece of chewed gum from the piano, wrapped it in her stage towel and put it in a Tower Records bag. The gum remained with him for twenty years. This book is about how something so small can form beautiful connections between people. It is a story about the meaning we place on things, on experiences, and how they become imbued with spirituality. It is a celebration of artistic process, friendship, understanding and love
Keywords: Simone, Nina -- 1933-2003; Kaugummi; Andenken; 65- / Art collections; Simone, Nina / 1933-2003; Souvenirs (Keepsakes); Collectors and collecting